Komparasi Visual Karakter Hero Video Game Mobile Legends dan Arena of Valor - Nurizki, Febi Amelia; Albar, Deni (DIVAGATRA - Jurnal Penelitian Mahasiswa Desain, 2024)
Video games have become a medium of entertainment that is needed by almost everyone. One of the most popular categories of online video games today is MOBA. Mobile Legends and Arena of Valor are examples of the most played MOBA games. These two games are similar in the visual aspect of their hero characters because they are inspired by predecessor characters such as legendary figures, mythological creatures, or even inspired by categories of creatures on earth which are then combined with humans. Mobile Legends has 4 hero characters that are visually similar to Arena of Valor. This makes both games modify, add, or even change the visual elements of each hero to avoid plagiarism. The modification of these heroes makes each character have its own impression/value. Analysis of visual elements is carried out by comparing the visuals of heroes from two games that are similar using matrix system theory so that the impression/value created by each visual can be found. The results of the visual analysis of the heroes of the two games that have been compared will determine which visual character is more suited to the impression presented.